Storage of boar semen at 17°C without conventional antibiotics in an extender containing an organic bactericidal substance - Luther, Anne-Marie; Nguyen, Thu Quynh; Verspohl, Jutta; Waberski, Dagmar (Frontiers in Veterinary Science, 2023)
Facing the global threat of antimicrobial resistance, the reduction of antibiotic use in semen extenders is a main goal in artificial insemination (AI) of pigs. The aim of this study was to investigate the potential of a commercial extender containing an organic bactericidal supplement in the absence of conventional antibiotics to control bacterial growth and to maintain the quality of boar spermatozoa during long-term semen storage for up to 144 h at 17 °C. For this, semen from 233 boars housed at 16 European AI centers was split and diluted in the long-term extender "Androstar Plus without antibiotics + organic bactericidal supplement" (APlus) and in the control extender Beltsville Thawing Solution (BTS) with gentamicin, which is routinely used in many AI centers. At the end of storage, bacterial counts were ≥ 10 6 CFU/mL in 10.7 % of the APlus and in 0.4 % of the BTS samples. At the same time, bacterial counts were only weakly correlated with sperm motility (r = -0.23, p<0.05), and there was no correlation with sperm membrane integrity (p> 0.05). Among the 12 identified bacterial species in APlus samples, loss of sperm quality was exclusively observed in the presence of >10 6 CFU/mL Serratia marcescens and Klebsiella oxytoca. Both these bacterial species, despite their known multi-drug resistance and the continuous use of gentamicin in Europe, proved sensitive to this antibiotic, thus indicating an efficient quality assurance program and responsible antibiotic use. In conclusion, long-term storage of boar semen at 17 °C without conventional antibiotics in an extender containing an organic bactericidal supplement is an option if semen samples are regularly tested for the presence of S. marcescens and K. oxytoca, and the source of contamination is eliminated.